A Methodology for the Marginalised: Surviving Oppression and Traumatic Fieldwork in the Neoliberal Academy. (August 2020) - Pearce, Ruth
This article proposes that survival may be considered a research method for social researchers, especially if they are undertaking fieldwork within marginalised communities of which they are a part. Drawing on an autoethnographic account of conducting research while trans, it shows how marginalised researchers may encounter both challenges common within the neoliberal university, and troubles specific to the researcher's social identity, touching on experiences of casualisation, distressing fieldwork, trauma, and suicide. The article concludes that marginalised researchers should not be held individually responsible for their own survival; rather, they require the active support of research communities and institutional frameworks.